Drug Distribution to Human Tissues: Prediction and Examination of the Basic Assumption in In Vivo Pharmacokinetics–Pharmacodynamics (PK/PD) Research. Issue 6 (25th March 2015) - Poulin, Patrick
<x xml:space="preserve">Abstract</x> The tissue:plasma partition coefficients (Kp) are good indicators of the extent of tissue distribution. Therefore, advanced tissue composition‐based models were used to predict the Kp values of drugs under in vivo conditions on the basis of in vitro and physiological input data. These models, however, focus on animal tissues and do not challenge the predictions with human tissues for drugs. The first objective of this study was to predict the experimentally determined Kp values of seven human tissues for 26 drugs. In all, 95% of the predicted Kp values are within 2.5‐fold error of the observed values in humans. Accordingly, these results suggest that the tissue composition‐based model used in this study is able to provide accurate estimates of drug partitioning in the studied human tissues. Furthermore, as the Kp equals to the ratio of total concentration between tissue and plasma, or the ratio of unbound fraction between plasma (fup) and tissue (fut), this parameter Kp would deviate from the unity. Therefore, the second objective was to examine the corresponding relationships between fup and fut values experimentally determined in humans for several drugs. The results also indicate that fup may significantly deviate to fut; the discrepancies are governed by the dissimilarities in the binding and ionization on both sides of the membrane, which were captured by the tissue composition‐based model. Hence, this violated the basic assumption in in vivo pharmacokinetics–pharmacodynamics (PK/PD) research, since the free drug concentration in tissue and plasma was not equal particularly for the ionizable drugs due to the pH gradient effect on the fraction of unionized drug in plasma (fuip) and tissue (fuit) (i.e., fup × fuip × total plasma concentration = fut × fuit× total tissue concentration, and, hence, the free drug concentration in plasma and tissue differed by fuip/fuit). Therefore, this assumption should be adjusted for the ionized drugs, and, hence, a mathematical correction to the basic assumption of similar free drug concentration in plasma and tissues can be derived from the tissue composition‐based model. Note that this assumption will be further challenged in a dynamic in vivo system in a companion manuscript. Overall, this study was a first attempt to predict the in vivo Kp values for specific human tissues by considering separately the effect of fup and fut, with the aim of facilitating the use of physiologically‐based PK (PBPK) model in PK/PD studies. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:2110–2118, 2015